Alchemy of wealth, information about traditional fertilization in Semnan province - alireza shahhosseini (Dānishhā-yi būmī-i Īrān, 2022)
One of the ways to strengthen agricultural land is to fertilize with animal and mineral fertilizers. This fertilization has made agricultural lands maintain their fertility without using chemical fertilizers. Therefore, in this article, the information of farmers and gardeners in different areas of Semnan province has been documented by the field method. In addition, in this research, all kinds of animal manures, including cow, sheep, camel, donkey, pigeon and chicken manure, which are known to be suitable for all kinds of agricultural and garden crops, have been collected. In the following, human manure, animal waste, green manure and the role of floods in strengthening and improving the quality of land are discussed. The studied areas were Abrasej of Shahroud, Armian of Miami, Garmsar plain, Hablerood and Semnan. The results show that the animal manures used based on the experiences of farmers have strengthened and enriched the land without harming it.